Let f(x)=3x+5 and g(x)=x^2 find (f-g)(x)

Asked 8 months ago
Viewed 846728 times
1
Let f(x)=3x+5 and g(x)=x^2 find (f-g)(x)

1 Answer

2

Answer:

(f - g)(x) = -x² + 3x + 5

General Formulas and Concepts:

Pre-Algebra

  • Equality Properties

Algebra I

  • Function Notation
  • Combining Like Terms

Step-by-step explanation:

Step 1: Define

f(x) = 3x + 5

g(x) = x²

(f - g)(x) is f(x) - g(x)

Step 2: Find (f - g)(x)

  1. Substitute:                   (f - g)(x) = 3x + 5 - x²
  2. Rewrite:                       (f - g)(x) = -x² + 3x + 5
Edit
avatar
answered 8 months ago